Odpowiedź :
[tex]|\frac{2}{3} *(\frac{1}{\sqrt{4} }-3\frac{2}{3}*1,5):\sqrt{\frac{4}{25}} |[/tex] = [tex]|\frac{2}{3}*(\frac{1}{2}-\frac{11}{3}*\frac{3}{2}):\frac{2}{5}|[/tex] = [tex]|\frac{2}{3}*(\frac{1}{2}-11*\frac{1}{2}):\frac{2}{5}|[/tex] = [tex]|\frac{2}{3}*(\frac{1}{2}-\frac{11}{2}):\frac{2}{5}|[/tex] = [tex]|\frac{2}{3}*(-5):\frac{2}{5}|[/tex] = [tex]|-\frac{2}{3}*5*\frac{5}{2}|[/tex] = [tex]|-\frac{1}{3}*5*5|[/tex] = [tex]|-\frac{25}{3}|[/tex] = [tex]\frac{25}{3}[/tex]
35%= 0,35
[tex]\frac{25}{3}[/tex] * 0,35 = [tex]\frac{35}{12} = 2\frac{11}{12}[/tex]